Avaliação da secagem, torrefação e estabilidade da castanha de pequi (Caryocar brasiliense Camb.) - RABÊLO, Ana Maria da Silva (2007)
Pequi (Caryocar brasiliense Camb.) possesss in its interior eatable chestnut little explored. In this study it was objectified to evaluate the drying process, toasting and the stability of the chestnut during 180 days in three different packings. Seeds supplied for the Association of Improvement of Fruits of the Open pasture, located in the city of Damianópolis-GO had been used. For extration of the chestnut equipment was adapted type guillotine, with purpose to cut the seed to the way. To determine curves of drying and toasting of chestnut greenhouse of drying with forced air circulation was used. For determination of optimum time of toasting the samples had been submitted to the sensorial evaluation. From the preferred sample more the centesimal composition was determined, sensorial and microbiological evaluation, profile acid greasy and physicist-chemistries, during the stockage. For drying of chestnut temperature of 70ºC per 60 minutes was used the pair time/, therefore it conferred to the product activity of water around 0,60 in lesser time drying. The roasted chestnut 130ºC during 15 and 30 minutes had been presented with better sensorial characteristics, not differing significantly between itself (p>0,05) for the Test of Friedman. The time of 30 minutes presented better sensorial characteristics, as color and crunchiness in the end item, although not to differ from the time of 15 minutes (p>0,05). The centesimal composition and of acid greasy was presented similar of other types of chestnuts. The evaluations physicist-chemistries of acidity, peroxide index, acid tiobarbituric, activity of water, humidity and the counting standard of bacteria in plates had inside presented of the standards established for all the treatments during the storage, as well as had been considered accepted in the carried through sensorial tests. The processes of definitive drying and toasting and the stability of the chestnut if had shown satisfactory in all the treatments during 180 days being able to be used by micron and small companies or cooperatives